From Golden Maknae to Global Soloist: A Narrative Study on Jungkook’s Artistic Journey - Amaliya Indah Permatasari (Grenek: Jurnal Seni Musik, 2025)
This article examines Jungkook’s artistic journey in his solo album Golden through a qualitative descriptive approach with narrative and thematic analysis methods. The Golden album is viewed not just as a musical work, but as an emotional narrative that displays a spectrum of experiences of love, loss, longing, and self-acceptance framed in the representation of lyrics, music videos, and media. Each song is analyzed as a form of expression of Jungkook’s identity that develops from the figure of BTS’s “Golden Maknae” to an autonomous and reflective global soloist. The research findings reveal that Golden's songs exhibit intertwined emotional and relational patterns, showcasing the psychological complexity and emotional maturity they offer to listeners. In addition, the audio-visual representation in the music video and Jungkook’s appearance in various international media strengthen the public’s interpretation of his new identity as a solo artist. This article highlights the importance of reading popular music works not only as entertainment products but also as narrative and emotional artifacts that mediate the relationship between artists and listeners in the context of global culture and the digital era.